Adaptive Educational Hypermedia Systems in the Advanced e-Services for the Knowledge Society (ASK) Research Unit of CERTH-ITI - Sampson, Demetrios; Karampiperis, Pythagoras; Manouselis, Nikos; Karagiannidis, Charalampos (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
ASK is an interdisciplinary unit engaged in research and development in Technology Enhanced Learning, and Semantic and Context-based Knowledge Systems. ASK's activities involve applied research, design and development of eservices for the knowledge society, as well as technology transfer, consulting and education.